The social ecological model of interpersonal health communication among rural older residents: a consensual qualitative study - Kong, Weijuan; Yang, Cailing; Li, Xinjin; Ning, Yanhua; Shi, Jing; Liu, Lingna; Liu, Haiyan; Guo, Yahong; Li, Meiman (Frontiers in Public Health, 2025)
ObjectivesTo explore the ecology of interpersonal health communication behavior among older residents in rural areas of western China.MethodsAdopted semi-structured interviews with 15 older residents and 15 family doctors in rural areas of five prefecture level cities in Ningxia Hui Autonomous Region, China. Used the Consensual Qualitative Research method for data analysis. Based on the ecological map drawn, understand how the interpersonal health communication behavior of older residents is carried and what factors affect it in rural area.ResultsAccording to the Ecological Systems Theory, we identified following themes: Microsystem (Weak recognition of health knowledge needs, Informal communication: mutual communication between relatives and friends and formal communication: one-way communication of family doctors); Mesosystem (Multi scenario and Multi channels); Exosystem (Medical environment and Family doctors’ workload) Macrosystem (National policies, Regional characteristics and Living environment).ConclusionIn summary, the health communication mode of older residents in rural areas is different from other populations, with face-to-face communication based on family doctors being the dominant mode and influenced by multiple levels of factors. Therefore, it is necessary to establish systematic plans at the policy, organizational, and other levels, especially in the training of family doctors, so that they can carry out more extensive and deeper professional interpersonal health communication, enhance the health literacy of the older, and maintain their health level.